2016
DOI: 10.1371/journal.pcbi.1005079
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of High-Order Metabolic Interactions to the Global Activity of a Four-Species Microbial Community

Abstract: The activity of a biological community is the outcome of complex processes involving interactions between community members. It is often unclear how to accurately incorporate these interactions into predictive models. Previous work has shown a range of positive and negative metabolic pairwise interactions between species. Here we examine the ability of a modified general Lotka-Volterra model with cell-cell interaction coefficients to predict the overall metabolic rate of a well-mixed microbial community compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 48 publications
3
61
2
Order By: Relevance
“…The predictions from pairwise experiments were significantly better compared to predictions based on single‐species growth. This finding agrees with work from our group (Friedman et al , ) and others (Guo & Boedicker, ) showing that pairwise outcomes are adequate for predicting multispecies community assembly and community‐level metabolic rates. In contrast to some theoretical work and empirical evidence (Bairey et al , ; Grilli et al , ; Mayfield & Stouffer, ), these results suggest that higher‐order interactions may play a relatively minor role in driving community assembly and that a network of pairwise interactions is an adequate description of the system.…”
Section: Interaction Network Of Microbiome Constructed From Pairwise supporting
confidence: 92%
“…The predictions from pairwise experiments were significantly better compared to predictions based on single‐species growth. This finding agrees with work from our group (Friedman et al , ) and others (Guo & Boedicker, ) showing that pairwise outcomes are adequate for predicting multispecies community assembly and community‐level metabolic rates. In contrast to some theoretical work and empirical evidence (Bairey et al , ; Grilli et al , ; Mayfield & Stouffer, ), these results suggest that higher‐order interactions may play a relatively minor role in driving community assembly and that a network of pairwise interactions is an adequate description of the system.…”
Section: Interaction Network Of Microbiome Constructed From Pairwise supporting
confidence: 92%
“…By contrast, history‐dependent responses were not detected in the synthetic consortium of eight soil isolates and coexistence was the prevalent community behavior (Friedman et al , ). On timescales of minutes, members of the freshwater isolate community did not display negative interactions that diminished cellular redox activity (Guo & Boedicker, ). Here, we interrogated the pairwise community dynamic behaviors in a 12‐member anaerobic community spanning four distinct phyla and observed frequent positive interactions and stable species coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial interactions have been probed in several synthetic ecologies of varying complexity and diversity including 18 Streptomyces strains (Wright & Vestigian, 2016), four-member freshwater isolates (Guo & Boedicker, 2016), and eight soil bacterial isolates composed of six strains from the Pseudomonas genus (Friedman et al, 2017). A significant fraction of the Streptomyces pairwise communities displayed frequent history-dependent and rare coexistence behaviors, which could be attributed to numerous mutual inhibitory pairwise interactions (Wright & Vestigian, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher-order interactions between more than two bacteria could potentially affect community stability (20), and the complexity of such interactions may limit the predictability of simple pairwise models (55). However, a recent study found that pairwise interactions largely predict the population dynamics of larger communities (56).…”
Section: Discussionmentioning
confidence: 99%